AN ANALYSIS OF PROBLEMS OF SUKANYA SAMRIDDHI ACCOUNT SCHEME: INVESTORS’ PERSPECTIVE - Ms. Jyoti Rani; Dr. Monika Malik; Dr. Pushpdeep Dagar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The main objectives of the study are to find out the major problems faced by the investors of Sukanya Samriddhi Account Scheme and to check the relationship between demographic variables and investment problems. A sample of 75 investors of SSA scheme from Rohtak city is selected. Mean, S.D., Ranking, and ANOVA techniques are used for analysis. The major problems are; the premature facility is not allowed, the loan facility is not available against the investment, and the long lock-in period. The Government of India should take certain measures to resolve these problems, so that more parents invest in this scheme.